Genetic characterization of the RAP-1A and SBP-4 genes of Babesia species infecting cattle from Selangor Malaysia, and Ribah, Nigeria - Gano, Adamu Isah; Ramanoon, Siti Zubaidah; Abdul Aziz, Nor-Azlina; Mazlan, Mazlina; Shaari, Mohd Rosly; Aliyu, Abdullahi; Bello, Muhammad Bashir; Imam, Mustapha Umar; Hamzah, Hazilawati (Multidisciplinary Digital Publishing Institute, 2024)
Bovine babesiosis has substantial economic implications in the cattle industry, emphasizing the need for a thorough understanding of the genetic diversity of the causative apicomplexan pathogen. Although babesiosis has been extensively studied globally, the genetic diversity of Babesia species in Malaysian and Nigerian cattle remains unreported. This study aims to bridge this gap by detecting and characterizing Babesia species in selected cattle herds. Our investigation explores the genetic diversity of Babesia species in cattle from Selangor, Malaysia, and Ribah, Nigeria. Blood samples revealed a 32.9% infection rate via PCR analysis. Further genetic analysis detected variations in Malaysian Babesia bigemina isolates but genetic similarity among Nigerian isolates. Conversely, all Babesia bovis isolates displayed genetic homogeneity. In summary, this research identifies genetic diversity in Babesia species affecting Malaysian and Nigerian cattle, highlighting regional disparities.